Strategi Komunikasi Penyuluh Agama Islam Dalam Pembinaan Masyarakat Kota Lhokseumawe - Muhajir (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2023)
This research is entitled "Communication Strategy of Islamic Religious Counselors in Community Religious Development in Lhokseumawe City". This title is interesting to study because of the intensive counselling activities by Islamic religious instructors today who are placed in District Religious Affairs offices throughout Indonesia. The existence of extension workers seems to only carry out work obligations but has not touched the realm of mediation in forming a sakinah mawaddah warahmah household. Using descriptive qualitative research, by selecting a number of resource persons from among the extension workers themselves who are considered capable of answering all problem formulations, both through oral interviews, attitudes and behaviours from among informants and selected research subjects. Data collection by interview, observation and documentation. From the results of research conducted by the author during this time for three months in the city of Lhokseumawe, shows that, communication strategies through cultural and historical approaches, social, legal. Opportunities and challenges faced due to religion economic problems, education and the low mindset of the people of Lhokseumawe.